Case Study Evaluations (GAO, 1990)
his guide from the US General Accounting Office outlines good practice in case study evaluation and establishes a set of principles for appl ying case studies to evaluations. The paper outlines new ways of think ing about case studies and examines the methodology necessary to get t he best from a case study analysis.